Função renal de cães hígidos tratados com anti-inflamatórios não-esteroidais - Borges, Marina (2011)
The anti-inflammatory nonsteroidal compounds have extremely widespread use in the therapy of small animals, due to their anti-inflammatory and analgesic properties. However, the use of these drugs can produce changes in kidney function. The present study was conducted to assess kidney function in healthy dogs undergoing therapy with anti-inflammatory nonsteroidal compounds. Thirty mongrel dogs, adults, males and females, clinically healthy, were divided randomly into 5 groups (G) of six animals each receiving the following therapies: Gceto ketoprofen, a 2 mg/kg dose (VO), every 24 hours, during 10 days; Gnime nimesulide, 5 mg/Kg, VO, every 24 hours, during 10 days; Gmelo- meloxican, 0.2 mg/Kg on the first day, followed by 0.1 mg/Kg, VO, every 24 hours, 7 days; Geto etodolac, 15 mg/Kg, VO, every 24 hours, 7 days; Gcele- celecoxibe, 5 mg/Kg, VO, every 12 hours, for 20 days. The physical examination and renal function (urinalysis, urinary GGT, creatinine and sodium, serum urea, creatinine, potassium and sodium, and endogenous creatinine clearance) were assessed prior to the treatment, on the 5th and 10th days (T0, T5 and T10) into the treatment in all groups, and also on the 20th day (T20) into the treatment in Gcele. Few changes were observed in urinalysis parameters, only with significant increase in the presence of renal cells in the urine in T5, in the nimesulide group. There was a significant reduction in sodium elimination in the animals urine in the nimesulide group. The clearance values showed significant decrease in the celecoxibe group in T20, in relation to T5. The enzyme GGT urinary showed no variation among groups or moments. Values of sodium, potassium, urea and creatinine serum remained within normal ranges in all times, in the different groups. In conclusion, minimal changes of renal function occur 10 days after therapy on set with NSAIDS nimesulide, after 10 days with ketoprofen, on the 20th days of therapy with celecoxibe in health dogs.